THE ESSENCE AND SPECIFIC FEATURES OF ENTREPRENEURIAL STRUCTURES’ STRATEGIC DEVELOPMENT - Lidiya S. Leont'eva; Anna V. Churashkina (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The aim of the article is to reveal the idea of the notion ‘entrepreneurial structures’ strategic development’. The author’s approach to this notion investigation is proposed, which uses methods of system analysis and systematization of development criteria. The author designed a three-level model of development criteria based on principles of their dependence and mutual deduction and substantiated the possibility to consider pair categories of quality and quantity, simple and complicated, regress and progress, activity and passivity, efficiency and inefficiency as development criteria. On this foundation the author formed understanding of entrepreneurial structures’ strategic development as a synthetic process of changing their activity and efficiency. According to the author, parameters of activity and efficiency are related to strategic characteristics and their change shows quantitative and qualitative aspects of entrepreneurial structures’ strategic development. It creates prerequisites for grounding assessment indicators characterizing the level and dynamics of activity and efficiency of entrepreneurial structures’ functioning and their integral assessment. The description of the process of entrepreneurial structures’ strategic development on the basis of these indicators can give an opportunity to resolve tasks of monitoring orientation and to raise the level of substantiation and assessment of consequences of strategic managerial decisions.